The influence of Total Quality Management and Reward on Employee Performance at Bank BJB Sumedang Branch Office - Nasution, Ade Iskandar; Dewi, Pebrianti Kamisha; Puspitasari, Melina Dwi (iora, 2023)
This study aims to determine how the effect of Total Quality Management and Reward on employee performance at Bank BJB Sumedang Branch Office either partially or simultaneously.The object of research on employee performance reports at Bank BJB Sumedang Branch Office. The type of research is quantitative associative with primary data type and uses data collection techniques in the form of observation, interviews, questionnaires, and literature study. While the sampling technique is Non Probability Sampling with purposive sampling. The population is all employees at Bank BJB Sumedang Branch Office, totaling 110 people with a sample of 86 people.The results showed that there was a significant effect on the Total Quality Management variable on Employee Performance of 57.5% at Bank BJB Sumedang Branch Office, this can be seen from tcount of 2,290 > 1,989 with a significant value of 0.025 < 0.05. There is a significant effect on the Reward variable on Employee Performance of 23.7% at Bank BJB Sumedang Branch Office, this can be seen from tcount of 2,076 > 1,989 with a significant value of 0.041 < 0.05. There is a simultaneous effect on the Total Quality Management and Reward variables on Employee Performance of 58.1% at Bank BJB Sumedang Branch Office, this can be seen from the Fcount of 7.214 > 2.71 and a significant value of 0.002 < 0.05, this indicates that independent variables jointly affect the dependent variable.